Efeito do pré aquecimento nas propriedades mecânicas e físicas de diferentes resinas compostas - NERY, Luanna Marinho Sereno (2018)
The preheating of composite resins arose with the aim of reducing the viscosity of resins with high inorganic filler content without compromising the properties of the polymerized material. Recently, the technique has been gaining popularity among dentists and there are heating devices being marketed for this purpose. The use of preheated resins to cement ceramic restorations would be interesting for the expansion of use, not only as a direct restorative material, but also as a luting agent, since it is part of the routine of dentists and is generally available in several dental offices. In the meantime, the viability of its use as luting material for ceramic laminates is unknown, since the studies are insufficient to support clinical recommendations. The purpose of the work was to study the effect of preheating of different resin composites, comparing them with dual-cured and resin cements, evaluating the mechanical and physical properties. Two types of composite resin (microhybrid and nanohybrid) were selected, as well as two composite resin cements (dual and light-cure). The preheating of the resins occurred by means of a proprietary device, preheating the resins at 69 ° C (± 1) in an average of 15 minutes, until the temperature stabilization, and then they were inserted in a single increment in the matrices of each test. These materials were subjected to tests of flexural strength, modulus of elasticity, fracture toughness, flow, sorption and solubility, translucency and color stability. Using the statistical data to verify the effect of the preheating in isolation for each type of resin, it was noticed that for the microhybrid resin (Z250), preheating generated an increase of the flow, sorption, modulus of elasticity, greater translucency in both water and wine, and greater color variation after 30 days of storage in water. No effect was found for the tests of flexural strength, fracture toughness, solubility and color variation after 30 days in wine. For the nanohybrid resin (Z350), there was an increase in the flow, sorption and high color variation after 30 days of storage for both water and wine, showing no other significant influence under the other properties tested. Finally, with the comparative analysis between the preheated resins and the resin cements, it can be verified that the flow of the cements continues higher, and these present even greater sorption and solubility, although the Z350 resin also presents high sorption and equivalent solubility to the CRD. Finally, regarding to the translucency and color stability, the cements presented higher translucency as a function of time, while the resins presented greater color variation as a function of the storage time, either in water or wine. For flexural strength and fracture toughness there was no statistical difference between these materials. We can conclude that the results show a positive effect of the preheaters under some mechanical properties of the composite resins analyzed. However, properties such as flexural strength and fracture toughness, which are defended as a great differential of the technique, and confer greater resistance to wear and tear. smaller deformation in the transfer of loads, do not present statistical differences of the resin cements. High sorption values, water and wine translucency, and color variation were observed for almost all the tests made for the microhybrid resin (Z250). Therefore, in order to deepen the knowledge about the subject, it is necessary to go beyond the laboratory tests that evaluate the intrinsic properties of the materials, later verifying their interaction with the dental substrate, in order to make in the future a preclinical study delineating the materials to be used, and then evaluate the behavior of these materials clinically in the long term.